4x ao quadrado - x +1 = x + 3x ao quadrado
Soluções para a tarefa
Respondido por
8
4x² - x + 1 - x - 3 x = 0
4x² - 5x + 1 = 0
| A = 4 | B = -5 | C = 1 |
Δ = -5² = 4 . 4 . 1
Δ = 25 = 16
Δ = 9 = √9 = 3
x =![\frac{-5 +- 3}{8}
\frac{-5 +- 3}{8}](https://tex.z-dn.net/?f=+%5Cfrac%7B-5+%2B-+3%7D%7B8%7D%0A+)
x¹ = 1
x² = 0.25
4x² - 5x + 1 = 0
| A = 4 | B = -5 | C = 1 |
Δ = -5² = 4 . 4 . 1
Δ = 25 = 16
Δ = 9 = √9 = 3
x =
x¹ = 1
x² = 0.25
x² + 5x + 4 = 0
| A = 1 | B = 5 | C = 4 |
x¹
x² = -4
Perguntas interessantes
Matemática,
1 ano atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Português,
1 ano atrás
História,
1 ano atrás
x² = Não existente